Value Stream Mapping Analysis: Case Study of Project Report Management in a Coal Mining Company - Bagus Hariyanto Pangestu; Mulyana Mulyana (Eduvest - Journal of Universal Studies, 2025)
This research explores the application of Value Stream Mapping (VSM) and Lean Management principles to enhance project performance reporting efficiency at PT Borneo Bara, a coal mining company in South Kalimantan, Indonesia. The coal mining industry faces significant challenges in project management, particularly in maintaining accurate, timely, and standardized reporting systems that are critical for operational decision-making and regulatory compliance. The current manual reporting process at PT Borneo Bara is characterized by inefficiencies, including extended processing times, data inaccuracies, and inconsistent formatting, which collectively hinder effective project monitoring and stakeholder communication. This study employs VSM analysis to systematically identify bottlenecks and waste in the existing reporting workflow. Through comprehensive process mapping and stakeholder interviews, the research identifies key obstacles, including redundant approval processes, manual data entry errors, and lack of standardized templates. A digital reporting system with automated validation and centralized data management is proposed as a solution. Implementation results demonstrate substantial improvements: reporting cycle time decreased from 10.8 days to 5.25 days (a 51.3% reduction), process efficiency increased from 44.1% to 90.5%, and data accuracy improved from low to high levels. These findings validate the effectiveness of VSM and Lean principles in streamlining project report management processes in the mining industry, offering practical implications for operational excellence and digital transformation initiatives.